Bulk Er:Yb:glass soliton femtosecond laser - Leuchs, Gerd; et al. (CLEO Technical digest, 2001)
A bulk solid state Erbium glass laser used to generate ultrashort laser pulses in the femtosecond regime was presented using soliton dynamics. Intracavity self-phase modulation was used to achieve soliton mode-locking. The dependence of pulse shaping dynamics on the pump power and intracavity dispersion was investigated, and the results were compared with the soliton mode-locking model.
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.bulker